The Relationship between First Trimester Serum Progesterone Levels and Spiral Artery Doppler Findings with Adverse Perinatal Outcomes - Ramazan Adan; Hicran Acar Şirinoğlu; Fatih Şahin; Savaş Özdemir (Clinical and Experimental Obstetrics & Gynecology)
Background: Progesterone is essential for maintaining pregnancy. Spiral arteries, providing blood flow to the placenta, undergo changes in early pregnancy, reducing uteroplacental resistance. Our study was aimed at investigating the relationship between the first trimester serum progesterone levels, spiral artery Doppler findings and pregnancy outcome. Methods: This observational retrospective cohort study included 126 pregnant women at 11–14 weeks of gestation, confirmed by last menstrual period and ultrasonography. Between 11–14 weeks, serum progesterone levels were measured and spiral artery pulsatility index (PI), resistive index (RI), peak systolic velocity (PSV) and systolic/diastolic ratio (S/D) values were recorded. Pregnant women were followed up until delivery, and serum progesterone levels and spiral artery Doppler findings were compared between patients with poor perinatal outcomes and others. Results: This study included 126 pregnancies, of which 13 patients were lost to follow-up. Miscarriage occurred in 2 of the pregnant women, stillbirth in 1, intrauterine growth retardation in 10 and preeclampsia in 5 of them. 6 infants developed respiratory problems and 3 infants developed jaundice. Seventeen of the infants were hospitalized in the neonatal intensive care unit. There was no statistically significant difference between serum progesterone, spiral artery PI, RI and S/D values of 86 uncomplicated and 27 complicated pregnant women. Conclusions: It is known that there is a strong relationship between the first trimester serum levels of progesterone, which is an important hormone for the healthy continuation of pregnancy, and the risk of miscarriage. The quantity and quality of placental and fetal circulation is determined by the changes that occur in the spiral arteries with pregnancy. Although a close relationship is known between both variables and pregnancy outcomes, no correlation could be established between them in terms of early detection of poor perinatal outcomes.